Contrasting Paternal and Maternal Genetic Histories of Thai and Lao Populations. (12th April 2019) - Kutanan, Wibhu; Kampuansai, Jatupol; Srikummool, Metawee; Brunelli, Andrea; Ghirotto, Silvia; Arias, Leonardo; Macholdt, Enrico; Hübner, Alexander; Schröder, Roland; Stoneking, Mark
Abstract: The human demographic history of Mainland Southeast Asia (MSEA) has not been well studied; in particular, there have been very few sequence-based studies of variation in the male-specific portions of the Y chromosome (MSY). Here, we report new MSY sequences of ∼2.3 mB from 914 males and combine these with previous data for a total of 928 MSY sequences belonging to 59 populations from Thailand and Laos who speak languages belonging to three major Mainland Southeast Asia families: Austroasiatic, Tai-Kadai, and Sino-Tibetan. Among the 92 MSY haplogroups, two main MSY lineages (O1b1a1a* [O-M95*] and O2a* [O-M324*]) contribute substantially to the paternal genetic makeup of Thailand and Laos. We also analyze complete mitochondrial DNA genome sequences published previously from the same groups and find contrasting pattern of male and female genetic variation and demographic expansions, especially for the hill tribes, Mon, and some major Thai groups. In particular, we detect an effect of postmarital residence pattern on genetic diversity in patrilocal versus matrilocal groups. Additionally, both male and female demographic expansions were observed during the early Mesolithic (∼10 ka), with two later major male-specific expansions during the Neolithic period (∼4–5 ka) and the Bronze/Iron Age (∼2.0–2.5 ka). These two later expansions are characteristic of the modern Austroasiatic and Tai-Kadai groups, respectively, consistent with recent ancient DNA studies. We simulate MSY data based on three demographic models (continuous migration, demic diffusion, and cultural diffusion) of major Thai groups and find different results from mitochondrial DNA simulations, supporting contrasting male and female genetic histories.